Pengaruh Insulasi pada Resistance Spot Weld dengan Elektroda Titik Ganda Celah Paralel Satu Sisi - Azwar Amat, Mohammad; Sifa, Agus; Dionisius, Felix; Endramawan, Tito; Apriyandi, D.D.; Rudiana (Journal of Applied Mechanical Technology, 2024)
Current leakage in parallel gap single-sided double spot welding tools occurs if the insulation to the mass-body, either from the work table or the drive system, can reduce the current concentration and result in double-sided welding being relatively difficult to carry out or the weld results being poor. Therefore in this research, an experiment was carried out to test the machine how big the effect of leakage current is on the quality of welded joints by comparing the strength of the joint between a system without insulation and a system using insulation using the independent sample t-test statistical method with a confidence level of 95%. The results of the study show that overall the max load for CT 3 to 10 is a mean difference between without and with insulation, although it is not very significant, this is because the shear test data from the group without insulation has quite a high deviation. High deviations also occur in the upper yield data, the strongest conclusion is that providing insulation (or preventing leakage current) provides a more consistent welding result as seen from the results of the shear test data. Only CT 3 has a significant impact on both max load and upper yield.